Multi-Criteria Performance Assessment of Rigid Pavement Concrete with High-Absorption Local Fine Aggregate Using Superplasticizer and Water-Reducing Admixture - Abdul Karim Hadi; Amalia Nur Chasanah (Three E Science Institute, 2026)
Rigid pavement concrete incorporating high-absorption local fine aggregate requires careful control of effective water availability, as aggregate moisture conditions may influence workability, setting behavior, and flexural performance. This study assessed the effects of superplasticizer and water-reducing admixture dosages on pavement concrete designed for a target compressive strength of 30 MPa and a target modulus of rupture of 45 kgf/cm² (4.41 MPa). A laboratory-based performance screening was conducted using a control mixture, superplasticizer mixtures at 0.60–1.50% by cement mass, water-reducing admixture mixtures at 0.15–0.35%, and one combined admixture mixture. Fresh properties were evaluated using slump, visual stability, bleeding and segregation observations, and initial setting time, whereas hardened performance was assessed through 7- and 28-day compressive and flexural strength tests. The control mixture achieved 31.71 MPa compressive strength at 28 days but failed the flexural strength requirement, reaching only 39.70 kgf/cm² (3.89 MPa). The 0.80% superplasticizer mixture achieved balanced performance, with 33.93 MPa compressive strength, 46.43 kgf/cm² (4.55 MPa) modulus of rupture, and an initial setting time of 4 hours. The 0.25% water-reducing admixture produced the highest compressive strength, 37.53 MPa, but did not meet the flexural criterion. The combined admixture mixture showed the best overall laboratory performance, achieving 33.75 MPa compressive strength, 56.90 kgf/cm² (5.58 MPa) modulus of rupture, and an initial setting time of 5 h 15 min. These findings indicate that pavement concrete mixture selection should integrate flexural strength, setting behavior, workability, and fresh-state stability rather than rely solely on compressive strength.